A harmonized HPTLC method for identification of various caffeine containing herbal drugs, extracts, and products, and quantitative estimation of their caffeine content. Issue 9 (15th June 2019) - Do, Tiên; Santi, Isaline; Reich, Eike
Abstract: Caffeine is an alkaloid used for long times in food, beverages, medicines, dietary supplements, and in botanicals such as coffee, cacao, cola, guarana, or tea. Today, more and more products are made with caffeine rich extracts from natural sources, or by adding caffeine. In order to prevent confusion about the origin of a caffeine-containing product, a specific method is needed for the determination of the botanical or chemical origin of the caffeine. As caffeine is known to be a central nervous system stimulant that can affect blood pressure and heart rate, all countries in the European Union require drinks (except tea and coffee) with more than 150 mg/L caffeine content to be labeled "high caffeine content", followed by their caffeine content expressed in mg/100 mL. The United States Department of Agriculture publishes food composition data including levels of caffeine in foods. Until now, there is no regulation for labeling the caffeine content of dietary supplements. This paper describes the development of a harmonized HPTLC method for the determination of the botanical origin of caffeine containing extract, and the detection of added caffeine in cases of adulteration. After identification, the verification of the caffeine content is necessary. In the absence of specific label information, the proposed method can be used to estimate the caffeine content of a product and where specific label information is present, it provides a limit test. GRAPHICAL ABSTRACT: